2021
DOI: 10.1016/j.scitotenv.2020.141790
|View full text |Cite
|
Sign up to set email alerts
|

‘Rotatinuous’ stocking as a climate-smart grazing management strategy for sheep production

Abstract: We aimed to evaluate the effect of different grazing management strategies on carcass characteristics traits, meat quality and CH4 intensity and yield of lambs grazing Italian ryegrass pastures in Southern Brazil. A grazing trial was performed (2014 and 2015) in a randomized complete block design with two grazing management targets and four replicates. Treatments were traditional rotational stocking (RT), with pre-and post-grazing sward heights of 25 and 5 cm, respectively, and 'Rotatinuous' stocking (RN), wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Carvalho [ 17 ] refers to this as the apparent trade-off of pasture management. However, previously, with temperate pastures [ 18 , 41 ] and in this work, with tropical forages, it is demonstrated that this classic trade-off can be overcome by adopting a LIHF, based upon animal-behavioral response as a function of sward structure (i.e., intake rate).…”
Section: Discussionmentioning
confidence: 81%
“…Carvalho [ 17 ] refers to this as the apparent trade-off of pasture management. However, previously, with temperate pastures [ 18 , 41 ] and in this work, with tropical forages, it is demonstrated that this classic trade-off can be overcome by adopting a LIHF, based upon animal-behavioral response as a function of sward structure (i.e., intake rate).…”
Section: Discussionmentioning
confidence: 81%
“…PISA is a reconciliatory solution model of blended good farming practices applied in a context-specific and holistic way aiming at agricultural development and sustainability. Integrated crop-livestock systems [34] , conservation agriculture [89] , climate-smart agriculture [90] , ecological intensification [88] , farm system design [91] , and the Rotatinuous stocking concept [92] are examples of technological frameworks that PISA promotes to accomplish parallel goals if saving land, reducing family workloads, producing more nutritious food and increasing farm profitability, in a customized site-by-site context. PISA is inspired by Nature and aims to be flexible and adaptable to any food production system in any part of the world.…”
Section: Brazilmentioning
confidence: 99%
“…The transition from current farming practices to ecological intensification is mediated through a strategic first step, which must be an intervention of no-cost, and at the same time, one that deeply affects all system functioning. The adoption of the Rotatinuous stocking concept [92,95] is a first step that enhances nutrient gathering from pasture and decreases the need for silage and concentrates, thus decreasing costs and family workloads. Milk production and quality increase in the short term.…”
Section: Brazilmentioning
confidence: 99%
“…For animals in this optimal pre-grazing SSH condition, high intake of highly digestible forage occurs, providing increases in feed conversion e ciency, carcass production and carcass quality and reductions in diet cost and enteric methane emissions (Savian et al 2018(Savian et al , 2021Zubieta et al 2021), all of which are criteria that should be prioritized in grazing management strategies. Parson et al (1988) discuss the defoliation process, based on the growth curve of plants under different intensities of sward depletion.…”
Section: Implications For Pasture Managementmentioning
confidence: 99%